Decolonizing 1968 : Transnational Student Activism in Tunis, Paris, and Dakar - Hendrickson, Burleigh J. (Burleigh Joe) (Book collections on Project MUSE., 2022)
"Traces the historical relationships between colonialism and 1968 activism, examining both the transnational networks that emerged and the new human and immigrants' rights initiatives that followed in their wake, and reveals 1968 not merely as a flashpoint in the history of left-wing protest but as a turning point in the history of decolonization"--